Teaching writing in economics. Issue 4 (2nd October 2017) - Schmeiser, Katherine
ABSTRACT: In this article, the author provides motivation and a template for integrating and teaching writing in a variety of economics courses: core theory or introductory courses, topic courses, and economic writing/research courses. For each assignment, pedagogical reasoning and syllabus integration are discussed. Additionally, the author shows that using grading practices and peer review as suggested in the literature can make the grading and time burden of teaching writing accessible to even large lecture courses.